2016
DOI: 10.1016/j.canlet.2016.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-derived ets factor represses tumorigenesis and modulates epithelial-to-mesenchymal transition in bladder carcinoma cells

Abstract: Prostate-derived Ets (E-twenty six) factor (PDEF), an epithelium-specific member of the Ets family of transcription factors, has been shown to play a role in suppressing the development of many epithelium-derived cancers such as prostate and breast cancer. It is not clear, however, whether PDEF is involved in the development or progression of bladder cancer. In a comparison between normal urothelium and bladder tumor tissue, we identified significant decreases of PDEF in the tumor tissue. Further, the immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 46 publications
2
38
1
Order By: Relevance
“…Maspin belongs to the serine protease inhibitor/noninhibitor superfamily and has dissimilar effects according to the types of cancer [4]. Although reports concerning the biological function of maspin in bladder cancer are still contradictory, our previous studies have indicated that maspin is the downstream gene of the prostate-derived Ets factor (PDEF) and growth differentiation factor 15 (GDF15), which are antitumor genes in bladder carcinoma cells [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maspin belongs to the serine protease inhibitor/noninhibitor superfamily and has dissimilar effects according to the types of cancer [4]. Although reports concerning the biological function of maspin in bladder cancer are still contradictory, our previous studies have indicated that maspin is the downstream gene of the prostate-derived Ets factor (PDEF) and growth differentiation factor 15 (GDF15), which are antitumor genes in bladder carcinoma cells [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The culture media were replaced with RPMI-1640 medium plus 10% FCS and 5 µg/mL polybrene (Santa Cruz Biotechnology, Santa Cruz, CA, USA) and transduced with maspin shRNA Lentiviral particles (sc-35859, Santa Cruz Biotechnology). Two days after transduction, the cells were selected by incubating with 10 µg/mL puromycin dihydrochloride for at least another three generations, as described in a previous study [19]. The p53-knockdown RT-4 (RT4_shp53), PTEN-knockdown RT-4 (RT4_shPTEN) and mock-knockdown RT-4 (RT4_shCOL) cells were cloned as described previously [39].…”
Section: Gene Knockdownmentioning
confidence: 99%
“…It has also been demonstrated that SPDEF acts as a tumor and metastasis suppressor in multiple epithelium‐derived cancers . For example, SPDEF inhibits survival of prostate cancer cells through the androgen receptor (AR) relevant for cancer signaling, suppresses colorectal cancer through the E‐cadherin and β‐catenin pathway, and modulates epithelial‐mesenchymal‐transition (EMT) to lower migration and invasion abilities of bladder carcinoma cells by upregulating E‐cadherin expression and downregulating the expression of N‐cadherin, SNAIL, SLUG, and vimentin . SPDEF is an important molecule for driving invasive mucinous adenocarcinoma of the lung (IMA) transformation …”
Section: Discussionmentioning
confidence: 99%
“…Cells were transiently transfected using the X-tremeGENE HP DNA transfection reagent (Roche Diagnostics, Indianapolis, IN) with 1 μg/well of reporter vector and 0.5 μg/well of the pCMVSPORTβgal (Invitrogen). The luciferase activity was adjusted for transfection efficiency using the normalization control plasmid pCMVSPORTβgal as previously described57.…”
Section: Methodsmentioning
confidence: 99%